2004
DOI: 10.1089/104303404323142006
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Controllable Activation of Suicide Gene Expression Driven by the Stress-InducibleGrp78Promoter Resulting in Eradication of Sizable Human Tumors

Abstract: GRP78 is a stress-inducible chaperone protein with antiapoptotic properties that is overexpressed in transformed cells and cells under glucose starvation, acidosis, and hypoxic conditions that persist in poorly vascularized tumors. Previously we demonstrated that the Grp78 promoter is able to eradicate tumors using murine cells in immunocompetent models by driving expression of the HSV-tk suicide gene. Here, through the use of positron emission tomography (PET) imaging, we provide direct evidence of spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 33 publications
2
80
0
Order By: Relevance
“…Robust induction of GRP78 occurs in many malignancies. 46 Furthermore, GRP78 has been shown to be involved in a number of physiological events that are key to tumor growth and survival. 47,48 Once upregulated or transcriptionally active, GRP78 can promote tumor proliferation through a variety of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Robust induction of GRP78 occurs in many malignancies. 46 Furthermore, GRP78 has been shown to be involved in a number of physiological events that are key to tumor growth and survival. 47,48 Once upregulated or transcriptionally active, GRP78 can promote tumor proliferation through a variety of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Grp78 has been implicated in the regulation of tumorigenesis. It has been shown that spontaneous activation of a reporter gene driven by the Grp78 promoter was found to be highly expressed in xenograft tumors in mice (31). Inhibition of Grp78 in xenografted fibrosarcoma suppressed tumor growth in mice presumably due to a cytotoxic T-cell response (32).…”
Section: Discussionmentioning
confidence: 99%
“…One promising therapeutic avenue entails the expression of a virally delivered cytotoxin under control of the ER stress-activated GRP78 promoter, which robustly eradicates human tumors in mouse xenograft experiments (99). Another approach is the development of small molecule-based therapies that directly inactivate key upstream activators of the UPR, such as PERK and Ire1, which are transmembrane kinases amenable to high-throughput screening for chemical inhibitors.…”
Section: Therapeutic Targeting Of the Upr In Cancermentioning
confidence: 99%